ChemInform Abstract: Fluoroferrates with (dabcoH2)2+ or (dabcoH)+ Cations. Issue 32 (24th July 2014) - Darmograi, Ganna; Jouffret, Laurent; Hemon‐Ribaud, Annie; Leblanc, Marc; Dujardin, Gilles; Maisonneuve, Vincent; Lhoste, Jerome
Abstract (H2DABCO) [FeIII2F8(H2O)2] (I), (H2DABCO)2 [FeIII2F10]·2H2O (II), (HDABCO)4 [FeIII2F10]·10H2O (III), and (HFDABCO)[(FeII(H2O)6) (FeIIIF6)] (IV) are prepared by conventional solvothermal synthesis using a EtOH or DMF solution of FeF2, FeF3, and HF (4%) with DABCO (autoclave, 120 °C, 72 h) to explore the composition space diagram of the (Fe2+, Fe3+)‐DABCO‐HFaq chemical system.